Primary Sellar Rhabdomyosarcoma Arising in Association With a Pituitary Adenoma. (December 2016) - Duncan, Virginia E.; Nabors, L. Burt; Warren, Paula P.; Conry, Robert M.; Willey, Christopher D.; Perry, Arie; Riley, Kristen O.; Hackney, James R.
Intrasellar rhabdomyosarcoma is rare, and when arising in collusion with an unrelated entity, can present a diagnostic pitfall. We describe a case of a 56-year-old woman who presented with right eye ptosis and a pituitary mass, which was resected and diagnosed as atypical pituitary adenoma. Because of residual disease and atypical pathology, the patient received adjuvant radiation. Tumor recurrence was noted after 5 months, and a second resection was performed. Nests of atypical pituitary adenoma cells within an exuberant spindle cell stroma were noted, with areas of presumed radiation necrosis. A second recurrence prompted a third resection. After expert consultation and additional immunohistochemical stains for muscle markers, a diagnosis was rendered of primary rhabdomyosarcoma arising in association with a pituitary adenoma. Despite its rarity, a high index of suspicion for rhabdomyosarcoma arising within a pituitary adenoma should be maintained in cases of atypical pituitary adenoma with a stromal response.